Fodor's Rome 2026 - Itzkowitz, Laura; Kennedy, Natalie (Fodor's full-color gold guides, 2026)
Whether you want to tour the Roman Forum, explore the Vatican, or marvel at the Colosseum, the local Fodor's travel experts in Rome are here to help! Fodor's Rome guidebook is packed with maps, carefully curated recommendations, and everything else you need to simplify your trip-planning process and make the most of your time. This new edition has been fully updated with an easy-to-read layout, fresh information, and beautiful color photographs. Fodor's Rome travel guide includes: An illustrated ultimate experiences guide to the top things to see and do; multiple itineraries to effectively organize your days and maximize your time; more than 20 detailed maps and a free pull-out map to help you navigate confidently; color photos throughout to spark your wanderlust! Honest recommendations from locals on the best sights, restaurants, hotels, nightlife, shopping, performing arts, activities, side-trips, and more; photo-filled "best of" features on "Best Museums," "Best Ancient Sites," "Best Churches," "Under-the-Radar Things to Do in Rome," and more; trip-planning tools and practical tips including when to go, getting around, beating the crowds, and saving time and money; historical and cultural insights providing rich context on the local people, politics, art, architecture, cuisine, music, geography, and more; special features on "The Sistine Chapel Ceiling" and "Ancient Rome Wasn't Built in a Day." Local writers to help you find the under-the-radar gems; Italian language primers with useful words and essential phrases; up-to-date coverage on: Vatican City, the Roman Forum, the Colosseum, St. Peter's Basilica, the Pantheon, Trastevere, Trevi Fountain, the Spanish Steps, and more.